The Existence and Dynamics of Muslim Minorities in Southeast Asia - Rahman, Bobbi Aidi (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2023)
Southeast Asia has the largest Muslim population in the world, although in this region the majority of the population is Muslim, but in some areas, there are also Muslim minority populations who are under non-Muslim rule, causing conflicts and disputes between groups that lead to intimidation, attacks, and mass killings. The purpose of this paper is to find out and analyze the conditions and development of Muslim minorities in Southeast Asia and the government's efforts to reduce conflicts that occur with a focus on three countries, namely Thailand, the Philippines and Myanmar. The condition of Muslim minorities under non-Muslim governments is certainly different from the condition of the Muslim-majority population under the rule of Muslim governments. This research is qualitative research, which collects various data and sources related to the study, both sourced from literature in the form of journal articles, books, and from the mass media using historical methods, namely heuristics, verification, interpretation and historiography. As for the findings of this study, the condition of Muslim minorities in Thailand and the Philippines despite pressure from the authorities, slowly began to be a concern of the government. However, in contrast to the condition of Muslim minorities in Myanmar, especially in Rohingya, they have not yet received recognition of their identity as citizens from the government and the Muslim side has always been concerned. Asia Tenggara merupakan penduduk Muslim yang terbesar di dunia, meskipun di wilayah ini penduduknya mayoritas Muslim, akan tetapi di sebagian wilayah terdapat juga penduduk minoritas Muslim yang berada dibawah pemerintahan non-Muslim, sehingga menimbulkan konflik dan pertikaian antar kelompok yang berujung pada intimidasi, serangan, dan pembunuhan massal. Adapun tujuan dari tulisan ini untuk mengetahui dan menganalisis kondisi dan perkembangan minoritas Muslim di Asia Tenggara serta upaya pemerintah dalam meredam konflik yang terjadi dengan fokus terhadap tiga negara, yakni Thailand, Filipina dan Myanmar. Kondisi minoritas Muslim dibawah pemerintahan non-Muslim tentunya berbeda dengan kondisi penduduk yang mayoritas Muslim di bawah kekuasan pemerintahan Muslim. Penelitian ini merupakan penelitian kualitatif, yakni mengumpulkan berbagai data dan sumber yang terkait dengan kajian, baik yang bersumber dari literatur-literatur berupa artikel jurnal, buku, maupun dari media massa dengan menggunakan metode sejarah, yaitu heuristik, verifikasi, interpretasi dan historiografi. Adapun hasil temuan kajian ini, bahwa kondisi minoritas Muslim di Thailand dan Filipina meskipun mendapat tekanan dari penguasa, namun dengan perlahan mereka mulai menjadi perhatian dari pemerintah. Akan tetapi, berbeda dengan kondisi minoritas Muslim di Myanmar, khususnya di Rohingya, mereka sama sekali belum mendapatkan pengakuan identitas sebagai warganegara dari pemerintah dan pihak Muslim selalu mengalami konflik yang tak kunjung selesai, meskipun beberapa organisasi internasional menjadi pihak penengah, namun konflik dan pertikaian tetap saja dialami oleh minoritas Muslim